Identifying Requirements for Vocational Information and Communication Technology Curricula in Afghanistan - Hedayati, Mohammad Hadi; Laanpere, Mart (Journal of Technical Education and Training, 2015)
This paper examines how ICT (Information & Communication Technology) is taught in vocational institutions in developing countries. If the world is truly flat, ICT education in Afghanistan and Namibia would. In the highly-standardized domain of ICT, the vocational education curricula should be similar to what you might find in Estonia and other developed nations. We focus specifically on what ICT with the consideration to the labour market needs, is the focus of this study. Such comparisons are demanding, because of the multiplicity of educational systems. Yet, there are some lessons we can learn from the international experience. CurrentICT qualification standards in Europe. The paper explores also current challenges in Afghanistan’s ICT Technical Vocational Education curricula, technical vocational institutes which influence the delivery of teaching and learning in ICT domain, as well as potential mismatch between the supply and demand of ICT-skilled workforce in Afghanistan.